SCALAR INTERACTIONS IN THE MODIFIED LEFT-RIGHT SYMMETRY MODEL - Istikomah, Istikomah; Isnawati, Nurul Embun; Sumarti, Heni; Anggita, Sheilla Rully (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2023)
The Standard Model is a model of particle physics in which one Higgs particle has been confirmed with a mass of 126 GeV. In 2016 some discoveries made it possible to have other scalar particles similar to the Higgs. The modified left-right symmetric model extends the standard model with an expanded scalar sector. There are ϕ_L and Δ_L left sector scalar particles, ϕ_L and Δ_L right sector scalar particles and two singlet η and ξ scalar particles. Therefore, this research objective is to analyze of the possibility of a Higgs interaction with other scalar particles. The method of this research is using a Feynman diagram to describe the interaction terms at the Higgs Potential. The interaction probability is sought using the Feynman rule for Toy Theory. The decay rate uses the Golden Rule. When the universe's temperature reaches the mass of η, the scalar becomes non-relativistic and decays into ϕ_L and ϕ_R. The scalar ξ is scattered into ϕ_L through the η scalar propagator and into ϕ_R. The scalars Δ_L and Δ_R do not decay, they only scatter into ϕ_L and ϕ_R. The η and ξ scalars have transformed into ϕ_L in the left sector and ϕ_R in the right sector, and only ϕ_L in the sectors are likely to be detected as the Higgs Standard Model.